Determinan Faktor Parenting Self-Efficacy (PSE) - Nursasmita, Rizqi; Asri Nurani, Intan; Anggarini, Diah; Ayu Amanda, Monica (NHM PRESS, 2023)
Parenting Self-Efficacy (PSE) is one of the parenting competencies. PSE is a cognitive construct that can be broadly defined as an individual's assessment of the competence of the parental role. The proper and effective role of parents is defined as the ability to carry out the roles of parents (father, mother and both) to have a positive influence on the behavior and development of their children. The purpose of this study was to determine the determinants of PSE factors in the Pasar Minggu Community Health Center area. The method used is descriptive quantitative cross-sectional. A high PSE has been shown to reduce depression, anxiety, stress in parents, poor behavior and better development in children. Conversely, a low PSE is considered to be a risk factor for negative parenting and poor parent-child relationships. This research will look at how PSE is owned by parents. The results showed that there was a significant relationship between parenting stress of parents (both mothers and fathers) with the ability of parents to care for their children.